(untitled) (Research, Society and Development, 2021)
This paper explores the premise that it is possible to adapt pedagogical approaches to the Remote Teaching model, given the limitation brough by the pandemic. In this context, 1st grade teachers at Escola Classe 304 Norte, in Brasilia, in the Federal District, shared their experience in relation to adaptations made to such pedagogical approaches. This research studies pedagogical approaches and practices, and adaptations tailored for remote teaching and its impact on children’s general learning outcomes. A qualitative research under an ethnographic scope was carried out through the systematic analysis of data collected by one the educators in her classroom work. It draws its theoretical basis on Social Sciences postulates, in particular ideas by André (1995), Sousa (2000), Libânio (2004), Klein and Pátaro (2008), Silva (2011), Souza and Serafim (2011), Veiga (2013) and Santos (2019). Results indicate that, although it is possible to employ technology resources to adapt pedagogical approaches and efficient and qualitatively improve children’s learning process, there are social-economic issues that directly interfere with such learning processes.